The risk of intra-urethral Foley catheter balloon inflation in spinal cord-injured patients: Lessons learned from a retrospective case series. Issue 1 (December 2016) - Subramanian, Vaidyanathan; Soni, Bakul; Hughes, Peter; Singh, Gurpreet; Oo, Tun
Abstract Background Inflating the balloon of Foley catheter in urethra is a complication of urethral catheterisation. We report five patients in whom this complication occurred because of unskilled catheterisation. Due to lack of awareness, the problem was not recognised promptly and patients came to harm. Case series 1. A tetraplegic patient developed pain in lower abdomen and became unwell after transurethral catheterisation. CT pelvis revealed full bladder with balloon of Foley catheter in dilated urethra. 2. Routine ultrasound examination in an asymptomatic tetraplegic patient with urethral catheter drainage, revealed Foley balloon in the urethra. He was advised to get catheterisations done by senior health professionals. 3. A paraplegic patient developed bleeding and bypassing after transurethral catheterisation. X-ray revealed Foley balloon in urethra; urethral catheter was changed ensuring its correct placement in urinary bladder. Subsequently, balloon of Foley catheter was inflated in urethra several times by community nurses, which resulted in erosion of bulbous urethra and urinary fistula. Suprapubic cystostomy was performed. 4. A tetraplegic patient developed sweating and increased spasms following urethral catheterisations. CT of abdomen revealed distended bladder with the balloon of Foley catheter located in urethra. Flexible cystoscopy and transurethral catheterisation over a guide-wire were performed. Patient noticed decrease in sweating and spasms. 5. A paraplegic patient developed lower abdominal pain and nausea following catheterisation. CT abdomen revealed bilateral hydronephrosis and hydroureter and Foley balloon located in urethra. Urehral catheterisation was performed over a guide-wire after cystoscopy. Subsequently suprapubic cystostomy was done. Conclusion Spinal cord injury patients are at increased risk for intra-urethral Foley catheter balloon inflation because of lack of sensation in urethra, urethral sphincter spasm, and false passage due to previous urethral trauma. Education and training of doctors and nurses in proper technique of catheterisation in spinal cord injury patients is vital to prevent intra-urethral inflation of Foley catheter balloon. If a spinal cord injury patient develops bypassing or symptoms of autonomic dysreflexia following catheterisation, incorrect placement of urethral catheter should be suspected.